La construcción de La Rioja sobre la base de la “soberanía de los Pueblos” en las primeras décadas del siglo XIX - Valentina Ayrolo (Nuevo mundo - Mundos Nuevos, 2023)
The aim of this article is to show some elements related to the political construction of the province of La Rioja in the first decades of the 19th century. It highlights the concern expressed by the Riojan elite in relation to the achievement of stability and governability of the province. Some administrative features are shown which reveal the interest of local leaders in organizing and controlling power from the headquarters in the city of La Rioja. The difficulties of this process are analyzed on the basis of the resistance shown by some towns to submit to the government based in the city.